Blackseafor: an attempt at regional security cooperation - Shyshko, Lesia; Шишко, Елизавета (My University, 2015)
This article deals with the security cooperation in the Black Sea, in the framework of the regional organization BLACKSEAFOR. The author analyzes the peculiarities of the Black Sea region building with introducing the historical context for its establishing. This is followed by an outline of the recent developments in the Black Sea states, the complexity of international relations, security challenges and military balance, thus explaining rationale behind establishing BLACKSEAFOR. Then, author characterizes new threats and challenges for the Black Sea states and gives an insight into functioning of the BLACKSEAFOR, the activities of this organization and how they corresponded to the proclaimed goals. The article concludes with present-day trends in the Black Sea region, and tries to answer the question, whether BLACKSEAFOR was an effective cooperation platform and what future prospects it might have.
Shyshko L/Blackseafor: an attempt at regional security cooperation / L. Shyshko // Актуальні проблеми політики зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), М. А. Польовий (відп. секр.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса : Фенікс, 2015. – Вип. 55. – С. 23-30.
Keywords: безопасность в Черном море в рамках организации Блэксифор; Черноморский регион; международные отношеня; проблемы безопасности и военного баланса; страны Черного моря; безпека в Чорному морі в рамках організації Блексіфор; Чорноморський регіон; міжнародні відносини; проблеми безпеки та військового балансу; країни Чорного моря; security in the Black Sea in the framework of the BLACKSEAFOR; The Black Sea region; international relationships; problems of security and military balance; Black Sea countries